A new species of Cordia (Cordiaceae, Boraginales) from Brazil - De Stapf, María Natividad Sánchez; Ranga, Neusa Taroda [UNESP]; Silva, Tǎnia Reginados Santos (Missouri Botanical Garden Press, 2010)
A new species from Brazil, Cordia pilosa M. Stapf & Taroda (Cordiaceae), is described from northeastern Brazil. Illustrations and data on habitat, distribution, and phenology are provided. The new species belongs to Cordia sect. Superbiflorae Taroda, and it is distinguished from similar species in section Superbiflorae by its compact inflorescences and the pilose indument on the twigs, leaves, and inflorescence axes. © 2010 Missouri Botanical Garden.
Keywords: Bahia; Brazil; Cordia; Cordiaceae; IUCN Red List